Development and Application of a Prophage Integrase Typing Scheme for Group B Streptococcus - Crestani, Chiara; Forde, Taya L.; Zadoks, Ruth N. (Frontiers in Microbiology, 2020)
Group B Streptococcus (GBS) is a gram-positive pathogen mainly affecting humans, cattle and fish. Mobile genetic elements play an important role in the evolution of GBS, its adaptation to host species and niches, and its pathogenicity. In particular, lysogenic prophages have been associated with a high virulence of certain strains and with their ability to cause invasive infections in humans. It is therefore important to be able to accurately detect and classify prophages in GBS genomes. Several bioinformatic tools for the identification of prophages in bacterial genomes are available on-line. However, genome searches for most of these programs are affected by the composition of their reference database. Lack of databases specific to GBS results in failure to recognize all prophages in the species. Additionally, performance of these programs is affected by genome fragmentation in the case of draft genomes, leading to underestimation of the number of phages. They also prove impractical when dealing with large genome datasets and they do not offer a quick way of classifying bacteriophages. We developed a GBS-specific method to screen genome assemblies for the presence of prophages and to classify them based on a reproducible typing scheme. This was achieved through an extensive search of a vast number of high-quality GBS sequences (n=593) originating from different host species and countries in order to build a database of phage integrase types, on which the scheme is based. The proposed typing scheme comprises twelve integration sites and sixteen prophage integrase types, including multiple subtypes per integration site and integrase genes that were not site-specific. Two putative phage-inducible chromosomal islands (PICI) and their insertion sites were also identified during the course of these analyses. Phages were common and diverse in all major clonal complexes associated with human disease and detected in isolates from every animal species and continent included in the study. This database will facilitate further work on the prevalence and role of prophages in GBS evolution, including in human carriage isolates and animal isolates, which are currently underrepresented in global databases.